Scrotal Swelling as a Complication of Hydrochlorothiazide Induced Acute Pancreatitis. (24th June 2015) - Nikiforov, Ivan; Mansoora, Qurat; Al-Khalisy, Hassan; Joseph, Sarah; Cheriyath, Pramil
Abstract : Background . Scrotal swelling is a rare complication of acute pancreatitis with few reported cases in the literature. In this case report, we present a 59-year-old male with hydrochlorothiazide induced pancreatitis who developed scrotal swelling. Case Presentation . A 59-year-old male presented to the emergency department with sharp epigastric abdominal pain that radiated to the back and chest. On physical examination, he had abdominal tenderness and distention with hypoactive bowel sounds. Computed tomography (CT) scan of the abdomen showed acute pancreatitis. The patient's condition deteriorated and he was admitted to the intensive care unit (ICU). After he improved and was transferred out of the ICU, the patient developed swelling of the scrotum and penis. Ultrasound (US) of the scrotum showed large hydrocele bilaterally with no varicoceles or testicular masses. Good blood flow was observed for both testicles. The swelling diminished over the next eight days with the addition of Lasix and the patient was discharged home in stable condition. Conclusion . Scrotal swelling is a rare complication of acute pancreatitis. It usually resolves spontaneously with conservative medical management such as diuretics and elevation of the legs.